The Legal Review of Tiktok Content Containing Photos and Videos of Sexual Harassment in Live Format (Perspective of ITE Law) - Taufik Hidayat; Nur Hilmiyah (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2024)
A legal review of TikTok's content of live open photos and videos from the perspective of the Electronic Information and Transaction Law (ITE) is one important aspect of efforts to regulate and protect internet users, especially children and adolescents, from harmful content. The ITE Law provides a relevant legal basis for responding to online safety violations, including the dissemination of sexualised content. The problems in the research are first, how is content containing sexual harassment in live format on TikTok created and disseminated? Second, how does TikTok content containing photos or videos of sexual harassment in live format affect users, especially teenagers in their psychology and behaviour? Third, how is the application of the law to Tiktok content containing sexual harassment? The purpose of this research is to answer the problems of this research. This research method is normative juridical research which focuses on secondary data in the form of primary, secondary, and tertiary data. The results of this discussion, among others, focus on content containing sexual harassment in live format on TikTok made and distributed can be charged with the ITE Law as Lex Specialist in conjunction with the Pornography Law, and the Criminal Code as the lex generalist. TikTok content containing photos or videos of sexual harassment in live format against users, especially teenagers in psychology and behaviour.